Influence Asset and Debt Policy to Tax Avoidance in Food and Beverage Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period - Situngkir, Gomgom; Pakpahan, Mario (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of asset intensity and debt policy on tax avoidance. To achieve this goal, research has been conducted on food and beverage companies listed on the Indonesia Stock Exchange. The population in this study consists of 26 food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Using the purposive sampling method, a sample of 13 companies was obtained. The research period consists of 5 years, starting from 2018-2022 so that the data amounts to 65. The data used in this study is secondary data, obtained from financial statements from www.idx.co.id website. The data obtained were in the form of secondary data, analyzed using descriptive statistical methods, classical assumption tests and multiple regression tests, while hypothesis tests were carried out using partial tests (T tests) and simultaneous tests (F tests). The results of the study partially show that asset intensity has a significant effect on tax avoidance with a significance value of 0.034 < 0.05, debt policy has a significant effect on tax avoidance with a significance value of 0.003 < 0.05, and asset intensity and debt policy simultaneously have a significant effect on tax avoidance with a significance value of 0.008 < 0.05. The conclusion of this study is that asset intensity and debt policy have a significant effect on partial tax avoidance. Simultaneously, asset intensity and debt policy have a significant effect on tax avoidance